2006
DOI: 10.1002/meet.14504301292
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on publicly hosted blog sites in the U.S., China, and Korea

Abstract: In the context of blogs, online trust can play an important role in connecting the author and readers. Trust is known to be one of the primary psychological aspects influencing online user profiling. In blogs, trust is reflected by how much personal information a user reveals. Trusting someone or something may be an entirely different matter in the United States than it is in China or Korea because trust affects actions that could be highly dependent on users' respective cultural context. This paper presents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The role of culture in determining the disclosure of gender has been highlighted by Park, Zhang, and Ma (2006), who found that only a minority of Chinese bloggers revealed their gender, far fewer than bloggers from the US and Korea; and by Gunawardena, Alami, Jayatilleke, and Bouachrine (2009) who compared the dynamics of swapping and concealing gender among Moroccan and Sri Lankan participants in Internet chat.…”
Section: Disclosure Of Gender Identity In Internet Forumsmentioning
confidence: 99%
“…The role of culture in determining the disclosure of gender has been highlighted by Park, Zhang, and Ma (2006), who found that only a minority of Chinese bloggers revealed their gender, far fewer than bloggers from the US and Korea; and by Gunawardena, Alami, Jayatilleke, and Bouachrine (2009) who compared the dynamics of swapping and concealing gender among Moroccan and Sri Lankan participants in Internet chat.…”
Section: Disclosure Of Gender Identity In Internet Forumsmentioning
confidence: 99%